2018
DOI: 10.1111/joss.12481
|View full text |Cite
|
Sign up to set email alerts
|

Comparing a full and reduced version of a consumer‐led lexicon to measure emotional response to beer

Abstract: Verbal self‐report emotion measures in sensory and consumer science commonly include a long lexicon of terms with an associated potential for participant boredom and fatigue. This study assessed the effectiveness of reducing the number of terms in a product‐specific lexicon by comparing a reduced form to a full form. The relative abilities of each lexicon to discriminate between beer samples were evaluated. Focus groups of UK beer consumers generated 43 emotion terms in response to a set of sensorially distinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Similar results were reported by Mora et al (2018) and were consistent with the first dimension of the circumplex model of emotions (Larsen & Diener, 1992;Russel, 1980;Watson & Tellegen, 1985). However, the second dimension of the present study (PC2) did not follow the theoretical model of previous literature and reported in other studies, in which a clearer relationship between PC2 and activation/arousal was evidenced for wine (Mora et al, 2018), blackcurrant squashes (Ng et al, 2013), beer (Chaya et al, 2015;Eaton et al, 2019, Mora et al, 2019, and coffee (Bhumiratana et al, 2014). Apparently, results from this research showed that the emotions associated with low or high activation were not so related to PC2 but were more combined with the valence axis (PC1).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar results were reported by Mora et al (2018) and were consistent with the first dimension of the circumplex model of emotions (Larsen & Diener, 1992;Russel, 1980;Watson & Tellegen, 1985). However, the second dimension of the present study (PC2) did not follow the theoretical model of previous literature and reported in other studies, in which a clearer relationship between PC2 and activation/arousal was evidenced for wine (Mora et al, 2018), blackcurrant squashes (Ng et al, 2013), beer (Chaya et al, 2015;Eaton et al, 2019, Mora et al, 2019, and coffee (Bhumiratana et al, 2014). Apparently, results from this research showed that the emotions associated with low or high activation were not so related to PC2 but were more combined with the valence axis (PC1).…”
Section: Discussionsupporting
confidence: 89%
“…For example, Chaya et al (2015) applied Hierarchical Cluster Analysis (HCA) to group terms with similar ratings into emotional categories, and to reduce the length of the questionnaire. The effectiveness of this approach was analyzed by Eaton, Chaya, Smart, and Hort (2019). Considering all these factors, when the emotional response elicited by food is assessed, specific "shorter/easier" questionnaires or methods belonging to the consumers' culture must be applied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data was collected using an online questionnaire via Compusense Cloud (Version 8.0.6288.23054, Compusense Inc., Guelph, Ontario, Canada). Participant's emotional response to each product was measured directly after tasting the beer using a previously developed beer specific emotion lexicon (Dorado et al, 2016;Eaton, Chaya, Smart, & Hort, 2018) consisting of ten emotion categories (Table 1). Each of the ten emotion categories was presented together with the associated terms and participants were asked to indicate the extent to which they were experiencing the emotions associated with those descriptors by giving an intensity rating on continuous line scale anchored from 'very low' to 'very high' at 5% and 95% of the scale.…”
Section: Questionnairesmentioning
confidence: 99%
“…During each session, participants reported their emotional response and liking for the beer (I) after the first sip, (II) after consuming half of the beer in the glass (approximately 142 ml) and (III) after consuming all of the beer in the glass (approximately 284 ml). A reduced beer specific emotion lexicon (Eaton, Chaya, Smart, & Hort, 2019) was used to determine emotional response at each consumption stage. The emotion terms for each category were presented together and participants were asked to rate each category on ten separate continuous line-scales of which the ends were labelled from 'very low' to 'very high' at 5% and 95% of the scale.…”
Section: Emotion Questionnairementioning
confidence: 99%